Potencialidades socioambientais das áreas de preservação permanente em fundos de vales urbanos: proposição de método expedito de análise - Pavezzi Netto, Milton (2013)
Guided by the questions about the effectiveness of strategies for environmental protection in cities, this research was aimed at structuring a fast method to analyze the social and environmental potential of PPAs in urban valley bottoms able to provide information to support the recovery and/or maintenance of the environmental quality of these areas in compatibility with existing social dynamics in the built space For structuring method, physical variables and criteria involved in the environmental quality of valley bottoms and representative forms of human occupation at these sites were raised. Based on these variables, we designed a scoring system that indicates the level of compliance with environmental functions of PPAs in urban valley bottoms and indicates the favorable and unfavorable conditions to fulfill these functions. The method was applied in two urban sources in the city of São Carlos, with distinct characteristics and land use in the buffer corresponding to the PPA. in the context of urban planning, the results of the application shows that the method has potential both to provide information that supports immediate or short-term decisions as to guide the application of other diagnostic decisions in the medium and long term.